Maternal Inflammation at Delivery Affects Assessment of Maternal Iron Status. Issue 10 (30th July 2014) - Lee, Sunmin; Guillet, Ronnie; Cooper, Elizabeth M.; Westerman, Mark; Orlando, Mark; Pressman, Eva; O'Brien, Kimberly O.
Abstract: Pregnant adolescents (aged ≤18 y, n = 253) were followed from ≥12 wk of gestation to delivery to assess longitudinal changes in anemia and iron status and to explore associations between iron status indicators, hepcidin, and inflammatory markers. Hemoglobin, soluble transferrin receptor (sTfR), ferritin, serum iron, erythropoietin (EPO), hepcidin, C-reactive protein, interleukin-6 (IL-6), folate, and vitamin B-12 were measured, and total body iron (TBI) (milligrams per kilogram) was calculated using sTfR and ferritin values. Anemia prevalence increased from trimesters 1 and 2 (3–5%, <28 wk) to trimester 3 (25%, 33.2 ± 3.7 wk, P < 0.0001). The prevalence of iron deficiency (sTfR > 8.5 mg/L) doubled from pregnancy to delivery (7% to 14%, P = 0.04). Ferritin and hepcidin concentrations at delivery may have been elevated as a consequence of inflammation because IL-6 concentrations at delivery were 1.6-fold higher than those obtained at 26.1 ± 3.3 wk of gestation ( P < 0.0001), and a positive association was found between IL-6 and both hepcidin and ferritin at delivery ( P < 0.01). EPO was consistently correlated with hemoglobin ( r = −0.36 and −0.43, P < 0.001), ferritin ( r = −0.37 and −0.32, P < 0.0001), sTfR ( r = 0.35 and 0.25, P < 0.001), TBI ( r = −0.44 and −0.37, P < 0.0001), and serum iron ( r = −0.22 and −0.16, P < 0.05) at mid-gestation and at delivery, respectively. EPO alone explained the largest proportion of variance in hemoglobin at 26.0 ± 3.3 wk of gestation ( R 2 = 0.13, P = 0.0001, n = 113) and at delivery ( R 2 = 0.19, P < 0.0001, n = 192). Pregnant adolescents are at high risk of anemia. EPO is a sensitive indicator of iron status across gestation, is not affected by systemic inflammation, and may better predict risk of anemia at term. The trial was registered at clinicaltrials.gov as NCT01019902.